Development of a high sensitive inductive movement sensor - Perederko, Anatolij (Eastern-European Journal of Enterprise Technologies, 2020)
Research on a contact induction displacement sensor over short distances is presented. A ferrite core with a winding and a movable armature is used as a sensor. There is an air gap between the core and the armature. To solve the problem of improving the accuracy of measurement, the sensor is included in the bridge measuring circuit, which is powered by high-frequency alternating current. To increase the sensitivity of the indicated sensor to movement, a differential circuit for its inclusion is proposed. Also, in order to increase sensitivity, the resonant mode of operation of the bridge measurement circuit is used. To maintain a constant voltage of the power generator, a phase-locked loop is used. As a result of the study of the induction displacement sensor, practical results were obtained with a maximum displacement of ±0.6 mm. The sensor has not been studied for large displacements, since with an increase in the indicated displacement, the nonlinearity of the displacement-current transformation appears. The maximum sensitivity of the differential sensor in the indicated range of movement 2.44 μA/μm is obtained without the use of a phase-locked loop. The use of a phase-locked-loop frequency adjustment system increased the sensitivity to 3.48 μA/μm. During the study, the dependence of the sensitivity of the sensor on the frequency of the power generator was determined, which allows to determine the optimal power frequency of the measuring bridge circuit. Studies have shown that the use of contact inductive meters have the prospect of application and reserves for improvement. And the use of differential inclusion of the sensor and the resonant mode of operation gives a significant increase in the sensitivity of the primary transducer at small displacements. An inexpensive sensor has been developed that will be useful for many applications where it is necessary to measure displacements and linear dimensions by contact methods